The Effect of Breathing Relaxation Techniques and Body Exercise on the Physical and Mental Readiness of Third Trimester Pregnant Women at PMB S - siti Asriyah; Wiwin Widyastuti (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: Pregnant women really need a fresh and fit body so they can carry out routines, practicing breathing relaxation techniques and body exercises (yoga) at this time are one of the self-help solutions that support the process of pregnancy, birth and child rearing. Purpose of Writing: to determine the effect of breathing relaxation techniques and body exercises on the physical and mental readiness of pregnant women in the third trimester Research Methods: This type of research uses a quasy experimental design with a one group pre-test post-test design, the sample in this study is 36 people in PMB S, Wilcoxon statistical analysis test. Research: There is an effect of breathing relaxation techniques and body exercise on the physical and mental readiness of third trimester pregnant women at PMB S with a p-value of 0.000 <0.05. Conclusions and Suggestions: This research is expected to increase knowledge about breathing relaxation techniques and body exercises as an effort to prepare pregnant women physically and mentally for childbirth.